2008
DOI: 10.1111/j.1365-2141.2008.07040.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine bone marrow derived stromal progenitor cells fail to prevent or treat acute graft‐versus‐host disease

Abstract: SummaryHuman and murine stromal progenitor cells (SPCs) can suppress alloresponse in vitro, suggesting that SPCs may have clinical application toward prevention or treatment of graft‐versus‐host disease (GVHD). However, th eresults of in vivo studies have been conflicting. This study utilized an established murine model of acute GVHD to assess the ability of bone marrow derived murine SPCs (mSPCs) to prevent or treat GVHD. GVHD was established by transplantation of B6 bone marrow and spleen cells into lethally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…In line with this, the results of our study also challenge the emerging concept that in humans iNOS has a pivotal role in MSC-mediated immunosuppression in vivo, 18 as in the human setting the role of IDO and others mechanisms appears more prominent. 2,[20][21][22][23] In addition, the outlined functional differences between murine and human MSCs might provide a clue to the partially discrepant results on the therapeutic efficacy of MSC obtained in preclinical murine models [24][25][26] and clinical studies. 27 From a clinical perspective, the identification of a cell autonomous antimicrobial effector function in human MSCs is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, the results of our study also challenge the emerging concept that in humans iNOS has a pivotal role in MSC-mediated immunosuppression in vivo, 18 as in the human setting the role of IDO and others mechanisms appears more prominent. 2,[20][21][22][23] In addition, the outlined functional differences between murine and human MSCs might provide a clue to the partially discrepant results on the therapeutic efficacy of MSC obtained in preclinical murine models [24][25][26] and clinical studies. 27 From a clinical perspective, the identification of a cell autonomous antimicrobial effector function in human MSCs is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…27 BM-MSC administration for treatment of GVHD did not improve long-term survival 23 and have also failed to show effects on GVHD in animal models. [28][29][30][31][32] Some studies from academic institutions have shown positive results, but there is most likely a selection bias in the literature as negative results are seldom published. 33 With all these concerns in mind, should we really use stromal cells as treatment for GVHD?…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these studies suggested that a single injection of (non-activated) MSC given on day 0 failed to prevent GVHD in most models [71,73,77,78], while a single infusion of activated MSC on day 0 [73], or repeated MSC injections at the time of and after transplantation showed clinical benefit in some [72,76,77] but not all [74,75,78] studies, depending on the GVHD model, the timing of MSC infusion, the dose of MSC infused, as well as the origin of MSC. However, repeated MSC injection failed to prevent lethal GVHD in a pre-clinical canine model of dog leukocyte antigen-haploidentical transplantation [79].…”
Section: New Cellular Approachesmentioning
confidence: 99%
“…A number of studies have assessed the ability of MSC infusion at preventing GVHD in various murine models of GVHD [71][72][73][74][75][76], in humanized murine models of xenogeneic GVHD [77,78], as well as in a preclinical canine model of GVHD [79]. Taken together, these studies suggested that a single injection of (non-activated) MSC given on day 0 failed to prevent GVHD in most models [71,73,77,78], while a single infusion of activated MSC on day 0 [73], or repeated MSC injections at the time of and after transplantation showed clinical benefit in some [72,76,77] but not all [74,75,78] studies, depending on the GVHD model, the timing of MSC infusion, the dose of MSC infused, as well as the origin of MSC.…”
Section: New Cellular Approachesmentioning
confidence: 99%